2011
DOI: 10.1007/s10447-011-9137-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Psychometric Properties of the Attitudes Toward Seeking Professional Psychological Help Scale-Short Form in Mainland China

Abstract: This investigation tested the psychometric properties of the Attitudes Toward Seeking Professional Psychological Help Scale-Short Form (ATSPPH-SF; Fisher and Farina [Journal of College Student Development, 36, 368-373, 1995]) in a sample of 338 Mainland Chinese college students. Using back-translation, the ATSPPH-SF was translated into simplified Chinese. Confirmatory factor analysis did not support the original one-factor model. Subsequently, exploratory factor analysis suggested a 7-item, two-factor model; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 78 publications
2
24
0
1
Order By: Relevance
“…Chinese cultural values emphasize interdependence, humility, emotional restraint, avoidance of shame, concern for face, and preservation of family honor [ 13 , 14 ], thereby possibly inducing discomfort in disclosing personal information to health professionals. The Chinese generally prefer to keep personal matters within the family rather than share such issues with outsiders; thus, this attitude may shape their help-seeking behaviors [ 15 , 16 ]. The ability to understand the helping relationships among the Chinese population may illuminate potential strategies to improve their health outcomes [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese cultural values emphasize interdependence, humility, emotional restraint, avoidance of shame, concern for face, and preservation of family honor [ 13 , 14 ], thereby possibly inducing discomfort in disclosing personal information to health professionals. The Chinese generally prefer to keep personal matters within the family rather than share such issues with outsiders; thus, this attitude may shape their help-seeking behaviors [ 15 , 16 ]. The ability to understand the helping relationships among the Chinese population may illuminate potential strategies to improve their health outcomes [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participant 6 explained that parents and teachers "just support[ed] you academically but not emotionally or mentally," suggesting a lack of understanding or awareness of mental health. This indicates that ATSPPH-SF and help-seeking attitudes in general may be affected by practical barriers particularly amongst Asian communities (Kung, 2004;Fang, Pieterse, Friedlander, & Cao, 2011), ranging from a lack of knowledge about the nature of counselling, lack of access to counselling services, to financial and language concerns.…”
Section: The Culture Of "Saving Face"mentioning
confidence: 99%
“…Some researchers found good internal consistency for a unidimensional measure (Ang et al, 2007), a two-factor model (Elhai et al, 2008), and a threefactor model (Picco et al, 2016) with two studies using Asian populations in Singapore (Ang et al, 2007;Picco et al, 2016). However, Fang, Pieterse, Friedlander, and Cao (2011) reported poor reliability coefficients for a Chinese population. This suggests some instability when using the measure on non-US participants as evidenced as well in Leach, Jana-Masri, and Priester's (2007) study on populations in Egypt.…”
Section: The Culture Of "Saving Face"mentioning
confidence: 99%
“…For instance, it has been suggested that norms about saving face and other cultural values reduce the likelihood of seeking help for psychological problems in China (Fang, Pieterse, Friedlander, & Cao, 2011). Contributing factors include concerns about stigma and self-stigma, and being raised in a culture that is less open about mental health issues.…”
Section: Factors That Contribute To Self-concealment and Perfectionismentioning
confidence: 99%